Redefining Tropical Walkability: The Challenge of Thermal Comfort for Captive Pedestrians in ITERA - Elisabet Nungky Septania; Stirena Rossy Tamariska; Galuh Fajarwati; Rabita Akbari Sitompul; Adelia Enjelina Matondang; Rendy Perdana Khidmat (Universitas Bandar Lampung (UBL), 2026)
University campuses in hot-humid tropical climates face complex challenges in balancing sustainability visions with user comfort. This study evaluates walkability at Institut Teknologi Sumatera (ITERA), a campus implementing vehicle restriction policies that effectively create a population of